2023
DOI: 10.2991/978-2-494069-99-2_12
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Bank Audit Committee and Risk-Taking Behavior. A Conceptual Framework

Abstract: This study intends to investigate the impact of bank audit committees' composite and bank risk-taking behavior in Malaysia from 2010 to 2019. The audit committee is accountable for assuring the accuracy of financial reporting disclosure, interacting with internal and external audit functions to strengthen the controls' function. The Islamic bank in Malaysia are required to adhere the Shariah compliance framework in their operational activities under the IFSA 2013. Following this, the Bank Negara of Malaysia (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Credit risk occurs when the actual loss exceeds the anticipated loss. The estimated loss was divided into several components, including expected Loss (Exposure to Default and Default Probability): "Loss due to default" Cheah et al (2023) identified these factors as the three main sources of credit risk. Risk at default refers to the amount legally owed to the lending bank at that moment.…”
Section: Introductionmentioning
confidence: 99%
“…Credit risk occurs when the actual loss exceeds the anticipated loss. The estimated loss was divided into several components, including expected Loss (Exposure to Default and Default Probability): "Loss due to default" Cheah et al (2023) identified these factors as the three main sources of credit risk. Risk at default refers to the amount legally owed to the lending bank at that moment.…”
Section: Introductionmentioning
confidence: 99%